Finance pathways for young innovative small‐ and medium‐size enterprises: A demand‐side examination of finance gaps and policy implications for the post‐global financial crisis finance escalator. (13th January 2019) - Owen, Robyn; Deakins, David; Savic, Maja
Abstract: The paper addresses the persistent finance gaps facing young, innovative SMEs, by examining the financing pathways of 40 UK businesses in a post global financial crisis (GFC) environment. Using a unique combination of finance escalator and resource‐based view theories four propositions are tested by examining: (i) early and growth stage development; (ii) innovation R&D investment horizons; (iii) the management resource base; (iv) finance gaps and their implications. The paper finds that successful financing strategies are emerging, using a mix of bootstrapping, collaboration and new emerging post‐GFC finance escalator funding, which is heavily reliant on government interventions. It also pinpoints remaining finance gaps and the need for more cohesive financing and support policy to address these.